2015
DOI: 10.22456/2178-8839.51761
|View full text |Cite
|
Sign up to set email alerts
|

Política Africana Do Brasil: Mudança Entre Lula E Dilma?

Abstract: IntroduçãoOs dois mandatos do governo Lula marcaram uma mudança significativa na política externa brasileira para a África. Depois de um longo distanciamento, as relações

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, with the arrival of Dilma Rousseff to the Presidency of the Republic it is observed that there was a distancing from international affairs and greater focus on domestic instabilities (Oliveira 2015). In 2014, Brazil entered a period of economic recession followed by a political crisis which culminated in the impeachment of Dilma Rousseff, in 2016 (Amorim Neto 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, with the arrival of Dilma Rousseff to the Presidency of the Republic it is observed that there was a distancing from international affairs and greater focus on domestic instabilities (Oliveira 2015). In 2014, Brazil entered a period of economic recession followed by a political crisis which culminated in the impeachment of Dilma Rousseff, in 2016 (Amorim Neto 2016).…”
Section: Introductionmentioning
confidence: 99%